(untitled) (Research, Society and Development, 2021)
The Court of Justice of Pernambuco (TJPE), since 2001, has maintained quotas in its public examinations to absorb and enhance the workforce of people with disabilities, and currently has 179 civil servants with some type of disability in its workforce. in different activities and sectors of the organization, throughout the State of Pernambuco. For a full professional performance, access to technological tools should serve all servers without distinction. The lack of adaptation of ICT services to TJPE servers with disabilities can lead to discouragement of its use, preventing the individual from exercising all their work potential by not fully taking advantage of the available technological tools. Within this context, the objective of the present work was to carry out a bibliographical survey on labor inclusion and the use of technological tools by the TJPE servers with disabilities, in order to seek solutions for an inclusive and accessible ICT service management. The documental research used the guidelines of the Prisma methodology, seeking historical legal understanding of labor inclusion, ICT practices for accessibility and experiences lived in the TJPE. This preliminary survey aims, in the future, to prepare a Booklet of Good Practices for the Management of ICT Services at the TJPE, for people with visual impairments. The results obtained showed that, although there is a movement to adapt technological tools to visually impaired servers at TJPE, there is still a need for a more effective and efficient management policy for the full labor utilization of these servers.